Stereotypy w przekładzie słowackich opowiadań Bajki dla niegrzecznych dzieci i ich troskliwych rodziców Dušana Taragela - Buczek, Marta (Przekłady Literatur Słowiańskich, 2013)
Stereotypes in the translation of Slovak short stories under the title Fairy Tales for Naughty Children and Their Caring Parents by Dušan Taragel The author of the article raises the problem of stereotypes in the Slovak collection of short stories book under the title Fairy Tales for Naughty Children and Their Caring Parents (1997) written by Dušan Taragel. The article focuses on the original text and its Polish translation by Tomasz Grabiński published in 2005. Dušan Taragel‘s short stories are an interesting example of using stereotypes in literature. He uses and forces well known sterotypes to perform tasks inconsistent with their basic semantics which leads to a transformation of the individual components of the stereotype and includes the new atypical structural relationships. Taragel’s short stories undertake a peculiar play with stereotypes using of the genre of the grotesque. An interesting matter is how the Polish translation deals with this and is carried out at all levels play. The article tries to answer the question if stereotypes may be translatable into the second language when the code changes, if they can be translatable in an act of cultural communication. Key words: Stereotype and translation, Slovak literature, Dušan Taragel, Tomasz Grabiński, Slovak literature in Poland.